2019
DOI: 10.1016/j.bpj.2019.01.041
|View full text |Cite|
|
Sign up to set email alerts
|

Force Spectroscopy Shows Dynamic Binding of Influenza Hemagglutinin and Neuraminidase to Sialic Acid

Abstract: The influenza A virus infects target cells through multivalent interactions of its major spike proteins, hemagglutinin (HA) and neuraminidase (NA), with the cellular receptor sialic acid (SA). HA is known to mediate the attachment of the virion to the cell, whereas NA enables the release of newly formed virions by cleaving SA from the cell. Because both proteins target the same receptor but have antagonistic functions, virus infection depends on a properly tuned balance of the kinetics of HA and NA activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 69 publications
4
49
1
Order By: Relevance
“…Although HA plays a crucial role in receptor binding and concurrent mutation capabilities, NA also has a key role in removing sialic acids from cellular receptors and from the new HA and NA on budding virions, which are sialylated as part of the glycosylation processes within the host cell ( 67 ). A balance between HA and NA is essential for viral fitness.…”
Section: Receptor Binding Of Virusesmentioning
confidence: 99%
“…Although HA plays a crucial role in receptor binding and concurrent mutation capabilities, NA also has a key role in removing sialic acids from cellular receptors and from the new HA and NA on budding virions, which are sialylated as part of the glycosylation processes within the host cell ( 67 ). A balance between HA and NA is essential for viral fitness.…”
Section: Receptor Binding Of Virusesmentioning
confidence: 99%
“…It has recently been reported that NA also enables virus movement on the cell surface toward endocytic sites, resulting in virus internalization for infection (14,15). Since both proteins target the same receptor, the functional activities of HA and NA need to be balanced for both virus entry into and virus release from host cells (16).…”
mentioning
confidence: 99%
“…In the absence of catalytic activity, NA can bind sialic acid with similar or even higher affinity compared to HA. [70,71] The receptor-binding function and the receptor-cleaving function of these two glycoproteins must be balanced for efficient transmission and proliferation of the virus. [3,4,72] This functional balance is also reflected in the evolution of HA and NA.…”
Section: The Influence Of Neuraminidase On Bindingmentioning
confidence: 99%